Examining the research and academic writing needs of preservice elementary teachers: a mixed-methods study - Hajan, Bonjovi Hassan; Radjuni, Abubakar Jaddal; Jemsy, Alhisan Utoh-asim (International Journal of Evaluation and Research in Education (IJERE), 2025)
In teacher education, research plays a central role in the preparation and professional development of preservice teachers. Preservice teachers’ knowledge of research and their academic writing skills serve as a pathway for successfully completing a research project. This sequential-explanatory mixed methods study was conducted to provide an in-depth understanding of the preservice elementary teachers’ needs on research and academic writing. A total of 80 preservice elementary teachers participated in the study. Data were collected online using a structured questionnaire and an interview guide. Drawing from both the quantitative and qualitative analyses, a multitude of the participants’ research and academic writing needs were uncovered. On the research component, the participants’ needs encompassed a wide range of areas, including knowledge of research methodology, access to quality data, expert support, among others. As for the academic writing, the participants’ needs varied from language use, structure and mechanics to the writing process. Based on the findings, the study outlines practical implications useful for teaching research writing within the context of teacher education.